How microRNA172 affects fruit growth in different species is dependent on fruit type. (2nd April 2016) - Yao, Jia-Long; Tomes, Sumathi; Xu, Juan; Gleave, Andrew P.
ABSTRACT: microRNA172 (miR172) expression has been shown to have a positive effect on Arabidopsis fruit (siliques) growth. In contrast, over-expression of miR172 has a negative influence on fruit growth in apple, resulting in a dramatic reduction in fruit size. This negative influence is supported by the results of analyzing a transposable element (TE) insertional allele of a MIR172 gene that has reduced expression of the miRNA and is associated with an increase in fruit size. Arabidopsis siliques are a dry fruit derived from ovary tissues, whereas apple is a fleshy pome fruit derived mostly from hypanthium tissues. A model has been developed to explain the contrasting impact of miR172 expression in these two plant species based on the differences in their fruit structure. Transgenic apple plants with extremely high levels of miR172 overexpression produced flowers consisting of carpel tissues only, which failed to produce fruit. By comparison, in tomato, a fleshy berry fruit derived from the ovary, high level over-expression of the same miR172 resulted in carpel-only flowers which developed into parthenocarpic fruit. These results further indicate that the influence of miR172 on fruit growth in different plant species depends on its fruit type.